Another Sogdian–Chinese bilingual epitaph*. (10th April 2017) - Bo, Bi; Sims-Williams, Nicholas; Yan, Yan
Abstract: Two stone tablets in the Wangye Museum, Shenzhen, contain a bilingual Sogdian and Chinese epitaph for a Sogdian merchant and his wife, who lived in the northern Chinese city of Ye 鄴 in the late sixth centuryce . The two texts are published here for the first time and accompanied by a detailed commentary on philological and historical points of interest.